Ultralow-density proppant based on solid waste compounding and preparation method of ultralow-density proppant

By using a composite preparation method of epoxy resin and solid waste powder, an ultra-low density proppant is generated, which solves the problem of sedimentation in traditional quartz sand and achieves efficient oil and gas well recovery and cost reduction.

CN120988685APending Publication Date: 2025-11-21LIAONING LONGYUAN SAND IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510806173.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In existing technologies, traditional quartz sand is prone to settling in hydroplaning fracturing systems, resulting in low recovery rates in unconventional oil and gas wells. Therefore, it is necessary to develop new ultra-low density proppant to solve the proppant migration problem.

Method used

An ultra-low density proppant is generated by mixing epoxy resin, diluent, silane coupling agent and solid waste powder, adding curing agent and surfactant, and reacting through heating and stirring. The solid waste powder is used as a filler to improve strength and reduce density.

Benefits of technology

The prepared proppant does not easily settle in low-viscosity hydroplaning fracturing fluid and can migrate to narrower fractures at the far end, improving oil and gas field recovery. It is low in cost and high in strength, making it suitable for hydroplaning fracturing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120988685A_ABST
    Figure CN120988685A_ABST
Patent Text Reader

Abstract

The invention provides an ultralow-density proppant based on solid waste compounding and a preparation method of the ultralow-density proppant, and belongs to the technical field of proppants. The preparation method comprises the following steps: uniformly mixing the epoxy resin, the diluent, the silane coupling agent and the solid waste powder, and aging to obtain a first mixed system; adding the curing agent and the surfactant into the deionized water, and stirring until the curing agent and the surfactant are completely dissolved to obtain a second mixed system; adding the second mixed system into the first mixed system at a preset temperature in a first stirring state, heating at the preset temperature, treating in a second stirring state until the reaction is finished, filtering, washing with clear water, and drying to obtain the ultralow-density proppant. The solid waste powder is adopted as the filler, the proppant cost is reduced while the strength of the proppant is improved, the liquid and the powder are used as the main raw materials to generate solid particles, and the resin is adopted as the main raw material to achieve the advantages of low density, high strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present disclosure belongs to the technical field of proppants, and particularly relates to an ultra-low density proppant based on solid waste composite and a preparation method thereof. BACKGROUND

[0002] Energy demand is rapidly increasing, while the availability of energy resources is becoming increasingly limited. In recent years, unconventional energy resources, such as shale gas, tight oil / gas or geothermal resources, have become important substitutes for conventional oil / gas resources. According to statistics, unconventional oil resources account for about 44% of the world's recoverable oil reserves, and unconventional natural gas resources account for about 25% of the recoverable natural gas reserves. Therefore, exploration of unconventional oil and gas reservoirs is crucial for future global energy supply.

[0003] However, the low porosity, low permeability and small pore throat radius of unconventional oil and gas reservoirs result in large flow resistance of oil and gas. Therefore, it is necessary to use reservoir stimulation methods such as hydraulic fracturing to develop and improve the overall reservoir permeability. Hydraulic fracturing is a process in which high-pressure fluid is pumped into an oil well (or gas well) at a high enough rate to create a fracture. Fracturing fluid introduces proppants into the fracture to ensure that the flow channel remains open. slickwater fracturing has been used in unconventional oil reservoirs as an alternative to guar gum fracturing technology and has achieved considerable success. However, the viscosity of slickwater fracturing fluid is very low, and it has poor ability to carry high-density proppants such as natural sand, ceramic and glass beads. Traditional quartz sand (density about 2.5 g / cm 3 ) is prone to sedimentation in a slickwater fracturing system and can only enter 20-30% of the fracture to play a supporting role, resulting in low recovery of unconventional gas and oil wells. Therefore, in order to solve the problem of proppant migration, it is necessary to develop new ultra-low density proppants. SUMMARY

[0004] The present disclosure aims to at least solve one of the technical problems existing in the prior art, and provides an ultra-low density proppant based on solid waste composite and a preparation method thereof.

[0005] In one aspect of the present disclosure, an ultra-low density proppant preparation method based on solid waste composite is provided, and the preparation method comprises:

[0006] Mixing the epoxy resin, diluent, silane coupling agent and solid waste powder uniformly and aging to obtain a first mixed system;

[0007] Adding the curing agent and surfactant to deionized water, stirring until completely dissolved to obtain a second mixed system;

[0008] The second mixed system is added to the first mixed system at a preset temperature and under a first stirring state, heated at the preset temperature and treated under a second stirring state until the reaction is completed, filtered, washed with clean water, and dried to obtain the ultra-low density proppant.

[0009] Optionally, the content of the epoxy resin is 10-30 parts by mass;

[0010] The content of the diluent is 10-30 parts by mass;

[0011] The content of the silane coupling agent is 0.1-0.3 parts by mass;

[0012] The content of the solid waste powder is 10-30 parts by mass;

[0013] The content of the curing agent is 2-5 parts by mass;

[0014] The content of the surfactant is 0.5-1.5 parts by mass.

[0015] Optionally, the content of the solid waste powder with a particle size of more than 45 μm is less than 12%.

[0016] Optionally, the aging time is 10-14 hours.

[0017] Optionally, the preset temperature is 35-45℃, and the heating time is 3-6 hours,

[0018] Optionally, the rotation speed of the first stirring is 100-200 r / min.

[0019] Optionally, the rotation speed of the second stirring is 150-250 r / min.

[0020] Optionally, the drying temperature is 50-70℃.

[0021] Another aspect of the present disclosure provides an ultra-low density proppant prepared by the method described above.

[0022] Optionally, the particle size of the ultra-low density proppant is 850-425 μm, the bulk density is 0.8-0.85 g / cm 3 , the apparent density is 1-1.3 g / cm 3 , the 69 MPa crushing rate is 1-1.3%, the turbidity is 10-10.3 NTU, and the acid solubility is 3-3.5%.

[0023] The disclosure provides an ultra-low density proppant based on solid waste composite and a preparation method thereof. The preparation method comprises the following steps: uniformly mixing epoxy resin, diluent, silane coupling agent and solid waste powder and aging to obtain a first mixed system; adding a curing agent and a surfactant to deionized water, stirring until completely dissolved to obtain a second mixed system; adding the second mixed system to the first mixed system under a preset temperature and a first stirring state, heating under the preset temperature and treating under a second stirring state until the reaction is completed, filtering, rinsing with clean water and drying to obtain the ultra-low density proppant. The disclosure uses solid waste powder as a filler to improve the strength of the proppant while reducing the cost of the proppant. In the preparation process, liquid and powder are used as main raw materials to generate solid particles, and resin is used as a main raw material to realize the advantages of low density and high strength. Moreover, the prepared proppant is not easy to settle in a low-viscosity slick water fracturing fluid, can be transported to a far-end narrow fracture, and can support a higher fracture volume, which is beneficial to slick water fracturing technology and can improve the recovery rate of oil and gas fields. BRIEF DESCRIPTION OF DRAWINGS

[0024] Figure 1 The flowchart of the preparation method of the ultra-low density proppant based on solid waste composite is shown in the specific embodiment of the disclosure. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solutions of the disclosure, the disclosure is further described in detail below in combination with the drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the disclosure and are part of the embodiments of the disclosure, but not all embodiments. Based on the embodiments of the disclosure, all other embodiments obtained by those skilled in the art without creative labor are within the protection scope of the disclosure.

[0026] As shown in the specific embodiment of the disclosure, Figure 1 An aspect of the disclosure provides a preparation method S100 of an ultra-low density proppant based on solid waste composite, which specifically comprises the following steps S110-S130:

[0027] S110, uniformly mixing epoxy resin, diluent, silane coupling agent and solid waste powder and aging to obtain a first mixed system.

[0028] Specifically, 10-30 parts by mass of epoxy resin, 10-30 parts by mass of diluent, 0.1-0.3 parts by mass of silane coupling agent and 10-30 parts by mass of solid waste powder are uniformly mixed and aged for 10-14 hours to promote the solid waste powder to be fully infiltrated, thereby obtaining the first mixed system.

[0029] In some preferred embodiments, the solid waste powder contains more than 88% particles with a diameter of less than 45 μm, meaning that most of the powder consists of particles smaller than 45 μm. This high proportion of fine particles makes it easier to disperse evenly and fully wet when mixed with epoxy resins, thus facilitating the formation of a stable mixture. Simultaneously, the smaller particle size increases the specific surface area of ​​the solid waste powder, resulting in a larger contact area with other components and a more complete reaction.

[0030] In some preferred embodiments, the solid waste powder can be commercially available fly ash, or other solid waste powders such as stainless steel slag powder, copper slag powder, red mud powder, silica fume, fly ash, etc., without specific limitations. These solid waste powders have low density, and their special structure and morphology can form pores or act as fillers in the system, reducing the proportion of high-density materials and lowering the overall density of the proppant to meet the requirements of ultra-low density. For example, commercially available fly ash is preferred, as its fine and porous structure helps to reduce the density of the proppant. In addition, the particles of these solid waste powders can also act as reinforcing phases, uniformly dispersed in matrices such as epoxy resin, playing a role in hindering crack propagation, thereby improving the compressive strength and wear resistance of the proppant, enabling it to withstand greater pressure and friction in complex underground environments, and ensuring the stability of oil and gas flow channels. Furthermore, using solid waste powders as raw materials realizes the reuse of solid waste, reduces the consumption of traditional raw materials, and lowers the preparation cost of the proppant.

[0031] In some other preferred embodiments, 692 diluent is used, which can effectively reduce the viscosity of epoxy resin and promote better mixing of epoxy resin and solid waste powder to form a stable system.

[0032] S120. Add the curing agent and surfactant to deionized water and stir until completely dissolved to obtain the second mixed system.

[0033] In some preferred embodiments, the curing agent is an epoxy resin curing agent, which can be triethylenetetramine, tertiary amine curing agent, etc., and the content can preferably be 2-5 parts by weight, for example, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, etc.

[0034] In some other preferred embodiments, the surfactant can be an emulsifier such as polyvinyl alcohol or polyethylene glycol, which promotes the formation of an emulsion when the aqueous solution is mixed with the epoxy resin solution, avoids epoxy resin agglomeration and precipitation, makes the components more uniformly distributed, improves the stability of the proppant performance, and at the same time, makes the emulsion better wet and adhere to the surface of the proppant material, which is conducive to the formation of a dense structure during the subsequent curing process, and improves the strength and durability of the proppant. The content can preferably be 0.5-1.5 parts by weight, for example, 0.5 parts by weight, 1.0 parts by weight, 1.5 parts by weight, etc.

[0035] S130, the second mixed system is added to the first mixed system at a preset temperature, heated at the preset temperature and treated at a second stirring state until the reaction is completed, filtered, washed with clean water, and dried to obtain the ultra-low density proppant.

[0036] Specifically, the second mixed system formed in step S120 is added into a beaker, then preheated to 35-45℃, the first mixed system formed in step S110 is added under stirring at 100-200r / min, and the stirring speed is kept at 150-250r / min, and heated at 35-45℃ for 3-6 hours. After the reaction is completed, the proppant is obtained by filtering, washing with clean water, and drying at 50-70℃.

[0037] The ultra-low density proppant prepared from waste in the embodiment uses solid waste powder as a filler to improve the strength while reducing the cost of the proppant, and uses resin as a main raw material to achieve the advantages of low density and high strength. In addition, in the preparation process, liquid and powder are used as main raw materials to form an oil-in-water emulsion under the action of stirring and emulsifiers, the filler wrapped by the epoxy resin is spherical, and the curing agent in the water phase promotes the curing of the epoxy resin to form solid particles.

[0038] The proppant prepared in the embodiment is not easy to settle in a low-viscosity slick water fracturing fluid, can be transported to a far-end narrow fracture, and can support a higher fracture volume, which is very beneficial to the slick water fracturing technology, can improve the recovery rate of oil and gas fields, and the ultra-low density proppant can increase the fracture support rate to more than 85%, and when the amount accounts for 2-5% of the mass of quartz sand, the recovery rate can be increased by at least 30%.

[0039] In another aspect of the disclosure, an ultra-low density proppant is provided, which is prepared by the method for preparing an ultra-low density proppant described above, and the specific process is described above and will not be repeated here.

[0040] In some preferred embodiments, the particle size of the ultra-low density proppant is 850-425μm, the bulk density is 0.8-0.85g / cm 3 , the apparent density is 1-1.3g / cm 3 , the 69MPa crushing rate is 1-1.3%, the turbidity is 10-10.3NTU, and the acid solubility is 3-3.5%.

[0041] The proppant of the embodiment has ultra-low density, high strength, and good acid, alkali and mineralized water resistance.

[0042] The preparation method of the ultra-low density proppant will be further described below with reference to specific embodiments.

[0043] Example 1

[0044] The preparation method of the ultra-low density proppant in this example includes the following steps:

[0045] S1, 20g of epoxy resin, 20g of 692 diluent, 0.2g of silane coupling agent, 20g of primary fly ash (particles above 45μm less than 12%) were mixed uniformly and aged for 12 hours to facilitate the full infiltration of the fly ash, to obtain a first mixed system.

[0046] S2, 4g of diethylene triamine, 1.0g of polyvinyl alcohol was added to 100mL of deionized water, stirred until completely dissolved, to obtain a second mixed system.

[0047] S3, the second mixed system was added to a beaker, then preheated to 40℃, 150r / min stirring state, the first mixed system was added, and the stirring speed was kept at 200r / min, heated at 40℃ for 4 hours. After the reaction was completed, it was filtered and washed with clean water, then dried at 60℃ to obtain the proppant.

[0048] The performance of the proppant of this example was evaluated according to SY / T5108-2014, wherein the volume density of the proppant with particle size in the range of 850-425μm was 0.82g / cm 3 , the apparent density was 1.22g / cm 3 , the 69MPa crushing rate was 1.23%, the turbidity was 10.2NTU, and the acid solubility was 3.4%.

[0049] Example 2

[0050] The preparation method of the ultra-low density proppant in this example includes the following steps:

[0051] S1, 20g of epoxy resin, 15g of 692 diluent, 0.2g of silane coupling agent, 20g of primary fly ash (particles above 45μm less than 12%) were mixed uniformly and aged for 12 hours to facilitate the full infiltration of the fly ash, to obtain a first mixed system.

[0052] S2, 3g of diethylene triamine, 1.0g of polyvinyl alcohol was added to 100mL of deionized water, stirred until completely dissolved, to obtain a second mixed system.

[0053] S3, the second mixed system was added to a beaker, then preheated to 40℃, 150r / min stirring state, the first mixed system was added, and the stirring speed was kept at 200r / min, heated at 40℃ for 4 hours. After the reaction was completed, it was filtered and washed with clean water, then dried at 60℃ to obtain the proppant.

[0054] The proppant performance of the present example is evaluated according to SY / T5108-2014, wherein the volume density of the proppant with a particle size in the range of 850-425 μm is 0.85 g / cm 3 , the apparent density is 1.25 g / cm 3 , the 69 MPa crushing rate is 1.15%, the turbidity is 13.2 NTU, and the acid solubility is 3.1%.

[0055] Example 3

[0056] The preparation method of the ultra-low density proppant in the present example includes the following steps:

[0057] S1, 20 g of epoxy resin, 15 g of 692 diluent, 0.2 g of silane coupling agent, and 10 g of primary fly ash (particles of 45 μm or more are less than 12%) are uniformly mixed and aged for 12 hours to facilitate the full infiltration of the fly ash, to obtain a first mixed system.

[0058] S2, 3 g of diethylenetriamine and 1.0 g of polyvinyl alcohol are added to 100 mL of deionized water, and stirred until completely dissolved to obtain a second mixed system.

[0059] S3, the second mixed system is added to a beaker, then preheated to 40°C, and the first mixed system is added under the condition of 150 r / min stirring, and the stirring speed is kept at 200 r / min, and the heating is kept at 40°C for 4 hours. After the reaction is completed, filter and rinse with clean water, then dry at 60°C to obtain the proppant.

[0060] The proppant performance of the present example is evaluated according to SY / T5108-2014, wherein the volume density of the proppant with a particle size in the range of 850-425 μm is 0.80 g / cm 3 , the apparent density is 1.15 g / cm 3 , the 69 MPa crushing rate is 1.29%, the turbidity is 10.9 NTU, and the acid solubility is 3.1%.

[0061] Example 4

[0062] The preparation method of the ultra-low density proppant in the present example includes the following steps:

[0063] S1, 20 g of epoxy resin, 15 g of 692 diluent, 0.2 g of silane coupling agent, and 10 g of primary fly ash (particles of 45 μm or more are less than 12%) are uniformly mixed and aged for 12 hours to facilitate the full infiltration of the fly ash, to obtain a first mixed system.

[0064] S2, 3 g of diethylenetriamine and 1.0 g of polyvinyl alcohol are added to 100 mL of deionized water, and stirred until completely dissolved to obtain a second mixed system.

[0065] S3, the second mixed system is added into a beaker, then preheated to 40°C, the first mixed system is added under the stirring state of 180 r / min, and the stirring speed is kept at 230 r / min all the time, and heated at 40°C for 5 hours. After the reaction is completed, filtration and washing with clean water are performed, and then the proppant is obtained by drying at 60°C.

[0066] The performance of the proppant of the example is evaluated according to SY / T5108-2014, wherein the volume density of the proppant with a particle size in the range of 850-425 μm is 0.80 g / cm 3 , the apparent density is 1.27 g / cm 3 , the 69 MPa crushing rate is 1.13%, the turbidity is 10.7 NTU, and the acid solubility is 3.9%.

[0067] Example 5

[0068] The preparation method of the ultra-low density proppant in the example includes the following steps:

[0069] S1, 20 g of epoxy resin, 20 g of 692 diluent, 0.2 g of silane coupling agent, and 20 g of primary fly ash (particles of 45 μm or more are less than 12%) are uniformly mixed and aged for 12 hours to allow the fly ash to be fully infiltrated, to obtain a first mixed system.

[0070] S2, 4 g of diethylene triamine and 1.0 g of polyethylene glycol are added to 100 mL of deionized water, and stirred until completely dissolved, to obtain a second mixed system.

[0071] S3, the second mixed system is added into a beaker, then preheated to 40°C, the first mixed system is added under the stirring state of 150 r / min, and the stirring speed is kept at 200 r / min all the time, and heated at 40°C for 4 hours. After the reaction is completed, filtration and washing with clean water are performed, and then the proppant is obtained by drying at 60°C.

[0072] The performance of the proppant of the example is evaluated according to SY / T5108-2014, wherein the volume density of the proppant with a particle size in the range of 850-425 μm is 0.83 g / cm 3 , the apparent density is 1.25 g / cm 3 , the 69 MPa crushing rate is 1.24%, the turbidity is 10.2 NTU, and the acid solubility is 3.3%.

[0073] Example 6

[0074] The preparation method of the ultra-low density proppant in the example includes the following steps:

[0075] S1, 20 g of epoxy resin, 20 g of 692 diluent, 0.2 g of silane coupling agent, 20 g of stainless steel slag powder (particles greater than 45 μm are less than 12%) are mixed uniformly and aged for 12 hours to allow the stainless steel slag powder to be fully infiltrated, to obtain a first mixed system.

[0076] S2, 4 g of diethylene triamine, 1.0 g of polyethylene glycol are added to 100 mL of deionized water, stirred until completely dissolved, to obtain a second mixed system.

[0077] S3, the second mixed system is added to a beaker, then preheated to 40℃, 150 r / min stirring state, the first mixed system is added, and the stirring speed is kept at 200 r / min, 40℃ heating for 4 hours. After the reaction is completed, filter and rinse with clean water, then dry at 60℃ to obtain the proppant.

[0078] The performance of the proppant of the embodiment is evaluated according to SY / T5108-2014, wherein the volume density of the proppant with a particle size in the range of 850-425 μm is 0.86 g / cm 3 , the apparent density is 1.29 g / cm 3 , the 69 MPa crushing rate is 1.14%, the turbidity is 10.7 NTU, and the acid solubility is 3.1%.

[0079] In summary, the super-low density proppant can be synthesized under the above conditions by using solid waste powder, and the volume density of the proppant is 0.80-0.86 g / cm 3 , the apparent density is 1.15-1.29 g / cm 3 , which is significantly lower than the density of conventional proppants, and is not easy to settle in the slickwater fracturing system, so that more proppants can enter the fracture to play a supporting role, which is beneficial to being carried to the target formation during oil and gas exploitation; secondly, the proppant has a low turbidity and a small amount of impurities, which reduces the pollution to oil and gas fluid, has high strength, can maintain structural stability in the complex high-pressure environment underground, effectively supports the formation pore, ensures the smoothness of the oil and gas flow channel, and prolongs the production life of the oil and gas well; in addition, it also has a moderate acid solubility, so that the proppant can be moderately dissolved when encountering acidic substances in the formation, thereby increasing the permeability of the formation and improving the oil and gas recovery.

[0080] The present disclosure proposes a super-low density proppant based on solid waste composite and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0081] Firstly, the present disclosure uses liquid and powder as main raw materials to generate solid particles, the raw material sources are widely available, and fly ash as industrial waste high-content solid waste can realize lower cost than resin balls,

[0082] Secondly, the resin is used as the main raw material to produce the proppant with low density and high strength, which is not easy to settle in the low viscosity slick water fracturing fluid.

[0083] It can be understood that the above embodiments are only exemplary embodiments adopted for illustrating the principles of the present disclosure, but the present disclosure is not limited thereto. Various modifications and improvements can be made by those of ordinary skill in the art without departing from the spirit and essence of the present disclosure, and these modifications and improvements are also considered as the protection scope of the present disclosure.

Claims

1. A method for preparing an ultra-low density proppant based on solid waste composite, characterized in that, The preparation method includes: The epoxy resin, diluent, silane coupling agent, and solid waste powder are mixed evenly and aged to obtain the first mixed system. Add the curing agent and surfactant to deionized water and stir until completely dissolved to obtain the second mixed system; The second mixture is added to the first mixture under a preset temperature and a first stirring state, heated at the preset temperature and processed under a second stirring state until the reaction is completed, filtered, rinsed with water, and dried to obtain an ultra-low density proppant.

2. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The content of the epoxy resin is 10-30 parts by weight; The content of the diluent is 10-30 parts by weight; The content of the silane coupling agent is 0.1-0.3 parts by weight; The content of the solid waste powder is 10-30 parts by weight; The content of the curing agent is 2-5 parts by weight; The content of the surfactant is 0.5-1.5 parts by weight.

3. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The content of the solid waste powder with a particle size of less than 45 μm is greater than 88%.

4. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The aging time is 10-14 hours.

5. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The preset temperature is 35-45℃, and the heating time is 3-6 hours.

6. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The first stirring speed is 100-200 r / min.

7. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The second stirring speed is 150-250 r / min.

8. The method for preparing ultra-low density proppant according to claim 1, characterized in that, The drying temperature is 50-70℃.

9. An ultra-low density proppant, characterized in that, The ultra-low density proppant is prepared using the ultra-low density proppant preparation method according to any one of claims 1 to 8.

10. The ultra-low density proppant according to claim 9, characterized in that, The ultra-low density proppant has a particle size of 850-425 μm and a bulk density of 0.8-0.85 g / cm³. 3 The apparent density is 1-1.3 g / cm³. 3 The breakage rate at 69 MPa is 1-1.3%, the turbidity is 10-10.3 NTU, and the acid solubility is 3-3.5%.